A Model of Engineering Education for Innovation - Sunthonkanokpong, Wisuit; Murphy, Elizabeth; Tuntrakool, Sunti (My University, 2018)
The purpose of this paper is to present implications of innovation for Engineering Education (EE) and research. The specific objectives are as follows: Analyze innovation policies from India, Malaysia, Thailand, Korea and the Association of South-East Nations (ASEAN): Identify common themes between policies; determine implications for EE for Innovation (EEFI); create a model of EEFI; determine implications for EEFI research. Analysis of the policies led to the identification of seven themes: prosperity, humanity, inclusivity, capacity, sustainability, inquiry, and community. These themes guided the creation of a model of EEFI. The model consists of four principal bases: learner-based; STEM + AE-based, problem-based and; project-based. Learner-based focuses on what engineers are in terms of their personal and professional competencies. STEM + AE are a reminder that engineers must be more than technicians, well-versed in STEM. Their education needs to include the arts and entrepreneurship. The problem base refers to EEFI activity being driven by complex, authentic, ill-structured challenges, problems and issues that have a social as well as a technical character. The project-base involves collaborative efforts to find answers to questions and create solutions to problems and challenges. Implications for research highlight a range of approaches to researching EEFI from quantitative surveys of perceptions of participants to complex research designs whereby engineers in training are collaboratively solving real problems in communities.
Keywords: Asia; Engineering education; higher education; innovation; model; pedagogy; research; STEM